High prevalence of sexually transmitted infections among asymptomatic women opting for the intrauterine contraceptive device use in Mwanza, Tanzania: An urgent call for control interventions. (May 2022) - Masatu, Emmanuel S; Kajura, Alphaxard; Mujuni, Fridolin; Chibwe, Elieza; Nyawale, Helmut A; Rambau, Peter; Majigo, Mtebe; Mshana, Stephen E.; Mirambo, Mariam M
Objective: Placement of intrauterine contraceptive device (IUCD) in asymptomatic woman infected with sexually transmitted infection (STIs) can lead to pelvic inflammatory diseases (PID) and infertility if not well treated. The current study investigated the magnitude of sexually transmitted infections among women opting for IUCD use in the city of Mwanza, Tanzania. Methods: A cross-sectional study involving 150 asymptomatic women was conducted from August to December 2017. Detection of Chlamydia trachomatis antigen from endocervical swabs was done using immunochromatographic rapid tests while sera were used for detection of Treponema pallidum, human immunodeficiency virus (HIV) and herpes simplex virus Type 2 (HSV-2) antibodies. Results: The overall prevalence of STIs was 45/150 (30%, 95% CI: 22–37) while that of individual STIs were 27.3%, 5.3%, and 2.6% for C trachomatis, T pallidum, and HSV-2, respectively. History of dysuria (aOR 6.6; 95% CI 2.3–18.8; p < 0.001) and history of STIs (aOR 4.6; 95%CI 1.0–20.8; p = 0.049) independently predicted presence of STIs. Conclusions: Prevalence of STIs among women opted for IUCD use in the city of Mwanza, Tanzania is alarmingly high and is predicted by past history of dysuria and history of partner's STIs, calling for the need of screening of the STIs among high-risk women in low- and middle-income countries (LMICs) opting for IUCD use.